Selection of patients with acute vertebrobasilar artery occlusion for endovascular treatment by magnetic resonance imaging - Chen, Jun; Zhang, Jiwei; Zhu, Xianjin; Zhang, Xuebin; Jiang, Bin; Liu, Qi; Wei, Zheng Z. (Frontiers in Neurology, 2023)
Background and purpose The best method for selecting patients with acute vertebrobasilar artery occlusion (VBAO) who would benefit from endovascular treatment (EVT) is still the key question. This study aimed to assess the efficacy of magnetic resonance imaging (MRI) for selecting patients with acute VBAO for EVT. Materials and methods A total of 14 patients with suspected acute VBAO on MR angiography (MRA) in the EVT database (from April 2016 to August 2019) were enrolled. Acute Stroke Prognosis Early Computed Tomography Score (ASPECTS) and pons–midbrain index were assessed on diffusion-weighted imaging (DWI). EVT included a stent retriever and a rescue treatment (angioplasty and/or stenting). The proportion of successful reperfusion and favorable functional outcomes (modified Rankin Scale ≤ 3) at 90 days was documented. Results A total of 11 patients were included in the final analysis. The median DWI-ASPECTS and pons–midbrain index were 7 and 2, respectively. Underlying stenosis was detected in 10 of 11 (90.9%) patients. Balloon angioplasty and/or stenting were used as rescue therapy for five patients and two patients, respectively. A total of nine patients (81.8%) achieved successful reperfusion (mTICI, 2b, or 3). The 90-day mRS score of 0–3 was achieved in six (54.5%) patients. The mortality rate within 90 days was 18.2% (two of 11 patients). Conclusion DWI plus MRA could help select the patients with acute VBAO for EVT by assessing ASPECTS and the pons–midbrain index. Patients could achieve good reperfusion and favorable functional outcomes.